PENGGUNAAN KUNINGAN SEBAGAI BAHAN CATALYTIC CONVERTER TERHADAP EMISI GAS BUANG dan PERFORMA MESIN SUZUKI SHOGUN AXELO 125 - Syahruji Syahruji; Abdul Ghofur (Scientific Journal of Mechanical Engineering Kinematika, 2019)
The purpose of this study was to determine the use of brass plate catalysts in the exhaust channel of Suzuki Shogun Axelo 125 in 2010. This study used an experimental method. The population in this study was a Suzuki Shogun Axelo 125 motorbike in 2010, the research data was a number showing gas content remove CO2, CO, HC. This research was carried out in the banjarmasin environment office using a gas analyzer and was also conducted at the Banjarmasin plug and play workshop by using a dynamometer. The technique used in data collection was the variation in rpm and number of plates. (1) The results of this study are: Forming a catalytic converter with plate variation 8 (eight) so that the level of CO2 emission reduction is maximum of 52,7%, the level of CO emission reduction is 82.23%, and the level of HC emission reduction is 74,08%. The form of catalytic converter with plate variation 6 (six), the maximum CO2 emission reduction level is 29,56%, the level of CO emission reduction is 49.32%, and the level of HC emission reduction is 82,92%. (2) By using catalytic converters with plate variation 8 (eight) to produce power of 8.045 hp and torque of 8,833 n / m and for catalytic converters with plate variation 6 (six) producing power of 7.661 hp and torque of 8.493 n / m.